REDUCTION OF BULLWHIP EFFECT ON COMMODITY SUPPLY CHAIN IN FRESH FRUITS AND VEGETABLES WHOLESALE LOTTEMART BOGOR - Bimahri Qaulan Tsaqiela; Yandra Arkeman; Bunasor Sanim (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
The purpose of this study was: (1) To identify supply chain structure of fresh fruit and vegetables in LotteMart Wholesale Bogor, (2) Analyze the value of bullwhip effect in the supply chain of fresh fruit and vegetables in LotteMart Wholesale Bogor. (3) Analyze the factors that led to the bullwhip effect in the supply chain of fresh fruit and vegetables at LotteMart Wholesale Bogor, (4) Reduce the bullwhip effect in the supply chain of fresh fruit and vegetables in LotteMart Wholesale Bogor. Method that used in this research are bullwhip effect formula to analyze the value of bullwhip effect and simulation to reduce bullwhip effect with software Arena Rockwell 14.0. The results showed that fresh fruit and vegetables in LotteMart Wholesale Bogor experienced bullwhip effect and also different scenario of time between arivals distribution able to reduce bullwhip effect value in supply chain.Keywords: supply chain, bullwhip effect, arena  simulation, LotteMart